Cortical Projection From the Premotor or Primary Motor Cortex to the Subthalamic Nucleus in Intact and Parkinsonian Adult Macaque Monkeys: A Pilot Tracing Study - Borgognon, Simon; Cottet, Jérôme; Badoud, Simon; Bloch, Jocelyne; Brunet, Jean-François; Rouiller, Eric M. (Frontiers in Neural Circuits, 2020)
Besides the main cortical inputs to the basal ganglia, via the corticostriatal projection, there is another input via the corticosubthalamic projection (CSTP), terminating in the subthalamic nucleus (STN). The present study investigated and compared the CSTPs originating from the premotor cortex (PM) or primary motor cortex (M1) in two groups of adult macaque monkeys. The first group includes six intact monkeys, whereas the second group was made up of four monkeys subjected to 1-methyl-4-phenyl-1,2,3,6- tetrahydropyridine (MPTP) intoxication producing Parkinson’s disease (PD)-like symptoms and subsequently treated with an autologous neural cell ecosystem (ANCE) therapy. The CSTPs were labelled with the anterograde tracer biotinylated dextran amine (BDA), injected either in PM or in M1. BDA labelled axonal terminal boutons in STN were charted, counted and then normalized based on the number of labelled corticospinal axons in each monkey. In intact monkeys, the CSTP from PM was denser than that originating from M1. In two PD monkeys, the CSTP originating from PM or from M1 were substantially increased, as compared to intact monkeys. In one other PD monkey, there was no obvious change, whereas the last PD monkey showed a decrease of the CSTP originating from M1. Interestingly, linear relationship between CSTP density and PD symptoms yielded a possible dependence of the CSTP re-organization with the severity of the MPTP lesion. The higher the PD symptoms, the larger the CSTP densities, irrespective of the origin (from both M1 or PM). Plasticity of the CSTP in PD monkeys may be related to PD itself and/or to the ANCE treatment.